(3GdEeJGY HCMcGe GdSeGYs - (3LYaQ Hf KYdH (B( (3JZdH(B) (3Hf LYaQ GdCOahj, CHh GdaVd, ceGd GdOjf,J (B748 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi HMeOI JJjSQ NajGJ GdCSQGQ , hHPcQI JWeFf GdbdhH hJfTQM GdUOhQ hJUah GdfahS ef GdCcOGQ hfTcQg HfUH CSQI GdSQhQ dHdhZ GdChWGQ s
(3BNQgG (B:s
(3hMaXhG TQjYJg YdjfG aai cd Ybhdge eff hdge MSfGJ cdeG LQi CMO Ydi Pdc GdSff , hYed HJdc GdSff GdPjf TfahG GdeSGeY HeMGSf GdcdGe hMQchG GdLhGQM HGdOYGA dge Ydi GdOhGe fLR GdcJGH GdeHGQc HMeO Gddg JYGdi hYhfg hMSf Jhajbg s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B167s
Keywords: (3Gdabg GdESdGejs